ANALISIS DISPERSION POWER PENALTY PADA AREA RING-1 JARINGAN LOKAL AKSES FIBER STO GATOT SUBROTO - Ningsih, Yuli Kurnia; Surjati, Indra; Sunarto, Sunarto; Hardianto, Herbowo (Jurnal Teknik Elektro, 2005)
Fiber attenuation caused by chromatic dispersion and modal dispersion is commonlyreferred to as a dispersion power penalty. In the wave transmitted by transmitter, dispersionoccurred, caused degradation of signal quality, so that the signal receiver is not as good aswhich is being transmitted. In this paper will be discussed about the impact of dispersionpower penalty in ring-1 STO Gatot Subroto area. Analysis was done to several factors thatcan cause dispersion power penalty, which are distance, wavelength, and data rate beingused. The calculation with available data and specification has been done, so that the routeswith the biggest and the smallest dispersion power penalty can be detected. The biggestdispersion power penalty happened in Palma Citra â Umawar route at distance of 9.387 kmwith ï¬ =1550 nm and data rate 622.08 Mbps. While the smallest was 1.221 7 10ï ï´ dB,happened in Tifa â STO Gatot Subroto route at distance of 1.626 km withï¬ =1310 nm anddata rate 155.52 Mbps. All those calculations were still in permissible limit, not more than 2dB. Furthermore from some routes were obtained very small dispersion power penalty. Thebigger the fiber length and data rate, the bigger the dispersion power penalty is. Finally itcan be concluded that fiber length, wavelength, and data rate are equivalent to thedispersion power penalty.Keyword: fiber optic, dispersion, Synchronous Digital Hierarchy